The Concept of Modern Islamic Education from the Perspective of K.H. Ahmad Dahlan: A Study of Progressive and Religious Values - Azizah, Lutfia Nur; Putra, Arizal Eka; Rohili, Tahir (Lembaga Riset Mutiara Akbar, 2025)
Islamic education in Indonesia faces the challenges of curriculum stagnation and a crisis of integration between religious values and modern science. K.H. Ahmad Dahlan, as the founder of Muhammadiyah, offered the idea of modern Islamic education that emphasizes the integration of progressive and religious values. This study aims to examine Ahmad Dahlan's thoughts in the context of contemporary Islamic education. The method used is a literature study of primary and secondary works, with a historical-critical approach. The results of the study indicate that Ahmad Dahlan's educational concept is transformative, combining the teachings of the Qur'an, active learning methods, and acceptance of modern science. The main findings reveal a gap between Ahmad Dahlan's idealism and current Islamic educational practices, especially in the aspects of value integration and digital literacy. The conclusion demonstrates the importance of recontextualizing Ahmad Dahlan's thoughts in designing an Islamic education system that is adaptive to the challenges of the times without abandoning spiritual values.